Illegal gold economy in peru: socioeconomic effects - Torres Cuzcano, Víctor (2014)
The paper analyzes the main developments operated in the domestic gold market so far this century. In particular, it stops at the deconcentration in the productionand export of this metal occurred amid the mining boom experienced by the country since late 2002 until very recently. It also discusses the expansion of illegal and informal gold mining, amid the sustained rise in the international price of gold that supported the mining boom and productive weakening of large mining. In this framework, quantified and valued the illegal and informal gold production and its impact on tax revenues.